Physicochemical Properties, Antioxidant Activities, and Aromatic Profile of Yogurt Co-Fermented by Weissella cibaria G232 with Traditional Starters - Qian Huang; Haixiao Ye; Yangyang Yang; Chenglin Zhu; Junni Tang (Foods)
To improve the quality and functional properties of yogurts, a multi-starters co-fermentation system was used during yogurt preparation. In this work, Weissella cibaria G232 (added at 0%, 3%, 5%, and 7%) was involved as a co-fermenter with a traditional starter (Lactobacillus delbrueckii subsp. bulgaricus G119 and Streptococcus thermophilus Q019). The results showed that W. cibaria G232 co-fermentation could shorten the fermentation time and significantly enhance the viable counts of yogurt (p < 0.05). Moreover, the incorporation of W. cibaria G232 improved the water holding ability, viscosity, and texture of yogurt. Notably, the highest levels of firmness, consistency, and cohesiveness of yogurt were observed at the 5% addition level of W. cibaria G232. Furthermore, co-fermentation with W. cibaria G232 significantly enhanced the antioxidant activity of yogurt, as evidenced by increased free radical scavenging capacity and ferric ion reducing antioxidant power (FRAP) value. The intelligent sensory technology and Gas Chromatography-Ion Mobility Spectrometry (GC-IMS) indicated that co-fermentation with W. cibaria G232 and a traditional starter notably altered the accumulation of aldehydes, ketones, and alcohols in yogurt. These findings suggest that co-fermentation of W. cibaria G232 with a traditional starter present the potential for the quality and functionality improvement of yogurt and also lay the foundation for the application of W. cibaria G232.